2019
DOI: 10.1161/atvbaha.119.313088
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Molecular Imaging of Atherosclerosis With Nanobodies

Abstract: Objective: Contrast-enhanced ultrasound molecular imaging (CEUMI) of endothelial expression of VCAM (vascular cell adhesion molecule)-1 could improve risk stratification for atherosclerosis. The microbubble contrast agents developed for preclinical studies are not suitable for clinical translation. Our aim was to characterize and validate a microbubble contrast agent using a clinically translatable single-variable domain immunoglobulin (nanobody) ligand. Approach a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Recently, cAbVCAM-1-5 has also been studied in CEU: Punjabi et al coupled anti-VCAM-1 nanobodies with microbubbles (MBcAbVCAM-1-5) to detect VCAM-1 expression in an atherosclerotic mouse model and ex vivo in human endarterectomy specimens using non-invasive ultrasound imaging. This study revealed that MBcAbVCAM-1-5 detected VCAM-1 expression in early and established atherosclerotic lesions in vivo and ex vivo, but it is not yet ready for clinical translation because the atherosclerosis developed in the mouse model studied is not similar to human atherosclerosis [106].…”
Section: Imaging Of Vcam-1mentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, cAbVCAM-1-5 has also been studied in CEU: Punjabi et al coupled anti-VCAM-1 nanobodies with microbubbles (MBcAbVCAM-1-5) to detect VCAM-1 expression in an atherosclerotic mouse model and ex vivo in human endarterectomy specimens using non-invasive ultrasound imaging. This study revealed that MBcAbVCAM-1-5 detected VCAM-1 expression in early and established atherosclerotic lesions in vivo and ex vivo, but it is not yet ready for clinical translation because the atherosclerosis developed in the mouse model studied is not similar to human atherosclerosis [106].…”
Section: Imaging Of Vcam-1mentioning
confidence: 92%
“…Detection of atherosclerotic lesions in the mouse aortic arch (Ao), near the heart (H), by in vivo β-CUBE imaging system after administration of [ 18 In summary, VCAM-1 imaging enables us to detect atherosclerotic plaques, stratify the risk and evaluate a new therapy in atherosclerosis in animal studies. Only a few studies [106,117] have demonstrated the efficiency of VCAM-1 targeting agents on ex vivo samples of human arteries.…”
Section: Imaging Of Vcam-1mentioning
confidence: 99%
“…An example of such a cardiovascular complication that can be detected from VCAM-1 expression is atherosclerotic disease, which can lead to stroke and myocardial infarction. While there has been some recent progress made in treating the acute or fatal complications of atherosclerosis, it has remained difficult to assess patient risk for the purpose of detecting abnormalities early on [ 131 ]. By detecting a clearly atherogenic phenotype before the disease progresses into its later stages, treatment protocols can be better catered towards reversing or stopping plaque formation, which is currently the leading reason for atherosclerotic mortality.…”
Section: Nanobodies As a Tool For Imaging Non-malignant Diseasementioning
confidence: 99%
“…Anti-VCAM-1 nanobodies were developed and conjugated to microbubbles to detect the VCAM-1 expression levels, both in mouse models of atherosclerosis and ex vivo human endarterectomy specimens [ 131 ]. These nanobodies were cross-reactive towards both murine and human VCAM-1, and the purpose of the microbubbles was to be used as a contrast agent for ultrasound imaging.…”
Section: Nanobodies As a Tool For Imaging Non-malignant Diseasementioning
confidence: 99%
See 1 more Smart Citation